1991
DOI: 10.1002/ijc.2910490226
|View full text |Cite
|
Sign up to set email alerts
|

Tumoricidal alveolar macrophage and tumor infiltrating macrophage cell lines

Abstract: Continuous alveolar macrophage (AM) and tumor-infiltrated (TIM) cell lines have been generated from C57B16J mice by in vitro infection with the J2 retrovirus carrying the v-raf and v-myc oncogens. Four cloned AM cell lines (AMJ2-C8, AMJ2-C10, AMJ2-C11, AMJ2-C20) and 3 cloned TIM cell lines (TIMJ2-C4, TIMJ2-C7 and TIMJ2-C15) were expanded for further characterization. Flow cytometry detected the product of the raf gene in the cytoplasm of all these cell lines. Studies on the tumoricidal properties of these AM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 21 publications
1
32
2
Order By: Relevance
“…When we sought to reproduce the dual LPS and IFN-7 requirement, we employed a range of LPS concentrations, without IFN-y, and then combined the maximum LPS concentration with 100 U/ml IFN-7. In contrast to the earlier report (19), we found that all three of the AM cell lines could produce TNF and IL-I[3 mRNA as early as 3 h after challenge with 10 gg/ml LPS alone, suggesting that these lines eould produce proinflammatory eytnkines without eostimulation by IFN-y (23). We extended our study to characterize these AM lines and their production of TNK IL-1]3, and IL-6 following stimulation with LPS and/or IFN-y, their TNF production in response to varying concentrations of LPS with and without serum, and their eonstitutive expression of the membrane LPS receptor, CD14 (mCD14) (33).…”
Section: Introductioncontrasting
confidence: 84%
See 4 more Smart Citations
“…When we sought to reproduce the dual LPS and IFN-7 requirement, we employed a range of LPS concentrations, without IFN-y, and then combined the maximum LPS concentration with 100 U/ml IFN-7. In contrast to the earlier report (19), we found that all three of the AM cell lines could produce TNF and IL-I[3 mRNA as early as 3 h after challenge with 10 gg/ml LPS alone, suggesting that these lines eould produce proinflammatory eytnkines without eostimulation by IFN-y (23). We extended our study to characterize these AM lines and their production of TNK IL-1]3, and IL-6 following stimulation with LPS and/or IFN-y, their TNF production in response to varying concentrations of LPS with and without serum, and their eonstitutive expression of the membrane LPS receptor, CD14 (mCD14) (33).…”
Section: Introductioncontrasting
confidence: 84%
“…AMJ2CS, AM52C11, and AMJ2C20 ceils were generously provided by Dr. Alicia Palleroni, Hoffman LaRoche (Nutley, NJ). These cells had been derived from C57B1/6J mouse AM transformed with recombinant J2 retrovirus (19). Cells were grown in Dulbecco's minimal essential medium (DMEM, BioWhittaker, Walkersville, MD) supplemented with 10% defined fetal bovine serum (FBS, Hyclone Laboratories, Logan, UT) and 5 mM HE-PES buffer (GIBCO, Grand Island, NY) at 37 ° C, in 5% CO2 and 95% humidity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations